Inhibition of Human Topoisomerase II by N, N, N‐Trimethylethanammonium Iodide Alkylcarbazole Derivatives. (30th November 2018) - Saturnino, Carmela; Caruso, Anna; Iacopetta, Domenico; Rosano, Camillo; Ceramella, Jessica; Muià, Noemi; Mariconda, Annaluisa; Bonomo, Maria Grazia; Ponassi, Marco; Rosace, Giuseppe; Sinicropi, Maria Stefania; Longo, Pasquale
Abstract: Chemotherapy is used for the treatment of all stages of breast cancer, including the metastatic stage of the disease. Treatment regimens are generally tailored for each patient′s particular situation. However, chemotherapeutic agents are the leading cause of serious drug‐related adverse effects; moreover, drug resistance often occurs. In this study, we designed and synthesized a new series of N ‐alkylcarbazoles derived from ellipticine, an alkaloid with a carbazole skeleton initially used in the treatment of metastatic breast cancer and later dismissed because of poor aqueous solubility and severe side effects. After evaluating the binding modes of our class of newly synthesized compounds with human topoisomerase II (hTopo II), we performed hTopo II decatenation assays, identifying compound4 f (2‐(4‐((3‐chloro‐9 H ‐carbazol‐9‐yl)pentyl)piperazin‐1‐yl)‐ N, N, N ‐trimethylethanammonium iodide) as a good inhibitor. Moreover, 4 f and4 g (2‐(4‐((3‐chloro‐9 H ‐carbazol‐9‐yl)hexyl)piperazin‐1‐yl)‐ N, N, N ‐trimethylethanammonium iodide) showed a good anti‐proliferative activity toward breast cancer cells, causing apoptosis by activation of the caspase pathway. Interestingly, the activity of these two compounds on triple‐negative MDA‐MB‐231 cells, which tend to be highly metastatic and aggressive, is strictly connected to the observed inhibition of hTopo II. Abstract : Cancer killers : New N, N, N ‐trimethylethanammonium iodide alkylcarbazole derivatives were synthesized and tested as human topoisomerase II inhibitors by in silico and in vitro studies. Compound4 f was found to be the most potent inhibitor and is able to trigger the intrinsic apoptotic pathway in MDA‐MB‐231 breast cancer cells.